CAPITAL ASSET PRICING MODEL: AN EVIDENCE OF RISK AND RETURN OF INVESTMENT OF COMPANIES AT FOOD AND BEVERAGE SUB SECTOR AT INDONESIA STOCK EXCHANGE - FRANCIS M. HUTABARAT; RUT NAOMI (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2018)
The economic development of a country surely is goal for any country. There are many ways that can be done to measure it, one of them by knowing the level of development of capital markets and securities industries in the country. This study aimed to measure and analyze food and beverage sub sector of the Indonesian Stock Exchange using Capital Asset Pricing Model. The sample used is active companies in stock transaction, such as: ADES, AISA, ALTO, CEKA, ICBP, INDF, MLBI, MYOR, ROTI, ULTJ listed in food and beverage sub sectors. Based on the results of the study, it can conclude that after analyzing the food and beverage sub sector of the Indonesian Stock Exchange using Capital Asset Pricing Model, Beta that is significant shows that the stock is worthy to invest, and they are AISA, INDF, ICBP and ROTI based on the period observed from January to March 2015. This indicate that in the first quarter of 2015, the four stocks shows great promises for investor to invest and out of the four, ICBP has positive rate of return.